Cai's prescription inhibits granulosa cell apoptosis through ARHGAP4 on poor ovarian responders - Zheng Wang; Denghao Liu; Yonghong Nie; Qinhua Zhang (BMC, 2024)
Abstract Purpose Poor ovarian response (POR) is a big challenge for in vitro fertilization. The traditional Chinese medicine, Cai's Prescription of Tonifying Kidney and Strengthening Vitals (Cai's Prescription) has yielded satisfactory results for POR treatment clinically, but systematic scientific research of Cai's Prescription is not well reported. This study aimed to investigate the clinical effect of Cai's Prescription on poor ovarian responders and its biological mechanism. Methods Serum was collected from poor ovarian responders, and IL-1β, INFγ, FSH, E2 and AMH levels were analyzed by ELISA. Ovarian antral follicles were identified and counted using transvaginal ultrasound. The embryo quality grading were done on day 3 after retrieval. We used high-throughput sequencing of granulosa cells to investigate the gene transcription patterns of ovarian granulosa cells in poor ovarian responders after Cai's Prescription pretreatment. The expression level of ARHGAP4 was analyzed by quantitative real-time PCR and western blot. The effects of ARHGAP4 for granulosa cells were analyzed by CCK-8 assay, annexin-V and PI staining, ELISA and western blot. The effects of Cai's Prescription on the expression of PI3K-Akt pathway and apoptosis were analyzed by western blot. Results In this study, we found that Cai's Prescription pretreatment had the tendency to improve the ovarian reserve function and could increase the number of high quality embryos for poor ovarian responders. Through high-throughput sequencing of mRNA in granulosa cells, we discovered ARHGAP4, which is a member of GTPase-activating proteins (GAPs) may be a candidate target for POR treatment. ARHGAP4 was significantly increased in poor ovarian responders and can be recovered after Cai's Prescription pretreatment. Mechanically, combining the cell line model and clinical tissue samples, we found that ARHGAP4 can accelerate cell apoptosis and inflammation response in granulosa cells via PI3K-Akt signaling pathway. In addition, Cai's Prescription pretreatment for three months significantly reduced the high level of ARHGAP4 in poor ovarian responders. Conclusion This study shows that the traditional Chinese medicine, Cai's Prescription yielded satisfactory results for poor ovarian responders clinically and ARHGAP4 may be a candidate target for POR treatment.